Reverse transcription-polymerase chain reaction (RT-PCR) assay for detection and characterization of Pea seed-borne mosaic virus in legumes applied by ICARDA’s GHU - Kumari, Safaa; Moukahel, Abdulrahman (International Center for Agricultural Research in the Dry Areas, 2022)
Pea seed-borne mosaic virus (PSbMV, genus Potyvirus, family Potyviridae) is the most important virus infecting lentil both in terms of economic importance and geographical distribution. It was reported that PSbMV can even lead up to 61% yield loss. Therefore, developing and implementing effective management strategies for PSbMV is very important to reduce yield and quality loss. However, accurate detection of virus disease is the first essential step for effective management strategies for control of this disease. Molecular is efficient tool to accurately detect and monitor the occurrence and development of crop diseases. This report describes a validated reverse transcription-polymerase chain reaction (RT-PCR) assay for PSbMV detection and characterization applied by ICARDA’s GHU.